Perancangan Sepatu Olahraga untuk Meningkatkan Keterampilan Anak dengan Balance Bike - Rizky Andana Reksaputra; Mohammad Djatmiko (Penerbit Itenas, 2024)
This project aims to design and produce balance bike sports shoes for children, emphasizing the protection of toes and heels, comfort, and optimal grip. With a concept focused on safety and comfort, these shoes feature special protective layers on the toes and heels, water-resistant and scratch-resistant materials, and cushioned, breathable insoles for maximum comfort. The shoe's outsole is crafted from high-quality rubber with an anti-slip tread pattern to ensure strong grip on various surfaces. The research employs the design thinking method, involving stages of empathy, definition, ideation, prototyping, and testing to understand user needs and develop suitable solutions. The results indicate that the designed shoes provide significant protection, all-day comfort, and the stability required by children when using balance bikes. This report details the design process, research findings, and recommendations for further production and improvements.